"A taste of elsewhere": Consuming the exotic in Simone Lazaroo's Sustenance. Issue 4 (4th July 2018) - Schwegler Castañer, Astrid
ABSTRACT: Simone Lazaroo's novel Sustenance (2010) explores Australian identity and its positioning of the Asian other, using the touristic setting of Bali to evidence the process of othering that takes place in Australian society, where acceptance of the other remains superficial and alterity is maintained. Through a close reading of Sustenance 's culinary extracts, this article argues that consumptive practices and the layering of stereotypes are used by Lazaroo to critically portray Australia's neocolonial relation to Asia as well as to evidence the downsides of the consumptive celebration of difference which blinds people to the realities of racism and intolerance. It explores how world views are transmitted through foodways, and how this feature of food is used in conflicting ways: by the local population and the tourists to generate interactions that rely on the mutual essentialization of cultural differences, and by the main character to underscore commonalities and to facilitate cross-cultural understanding.